Pemakaian Bahasa Jawa di Provinsi Lampung Bedasar Data Sensus Penduduk 2010 - Suyanto Suyanto; Mujid Farihul Amin (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
The study of this language is macro by using data from the census of Indonesian population 2010. The study included (a) the number of Javanese speakers in Lampung in 2010, (b) the factor of Javanese distribution in Lampung in 2010, and (c) and the influence Javanese in Lampung. Obtaining data using the method refer. Data analysis used descriptive statistical analysis using single frequency distribution table and continued with categorical analysis and interpreted theoretically various prominent phenomena. The results showed that spatially the population in Lampung more use of Javanese language than Lampung. In addition, the population proportion of migration Java population is more than the total population of Lampung. This is closely related to the migration program of the Javanese population that had begun since the Dutch colonial era up to the Soeharto era.